2014
DOI: 10.4103/0976-5042.150660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic profile of patients with upper gastrointestinal bleeding at tertiary care center of North India

Abstract: Background: Upper gastrointestinal bleeding (UGIB) is a common medical emergency associated with significant morbidity and mortality. The presentation of bleeding depends on the amount and location of hemorrhage and the endoscopic profile varies according to different etiology. Despite advancements in medical intervention UGIB still carries considerable morbidity, mortality and economic burden on health care system. At present, there is limited epidemiological data on UGIB and associated mortality from India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
(24 reference statements)
10
23
0
1
Order By: Relevance
“…Aetiological spectrum of UGIB showed that peptic ulcer disease was the most common cause, which is consistent with the study of Rocall et al 2 whereas in Indian studies portal hypertension-related UGIB was the most common cause. 11,13 The cause of portal hypertension is mostly due to alcohol-related liver disease in India 11,13 whereas in our study most common cause of portal hypertension was chronic liver disease due to hepatitis B. A significant portion of our patients presented with UGIB due to corrosive burn (harpic) which was mostly due to suicidal attempt.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Aetiological spectrum of UGIB showed that peptic ulcer disease was the most common cause, which is consistent with the study of Rocall et al 2 whereas in Indian studies portal hypertension-related UGIB was the most common cause. 11,13 The cause of portal hypertension is mostly due to alcohol-related liver disease in India 11,13 whereas in our study most common cause of portal hypertension was chronic liver disease due to hepatitis B. A significant portion of our patients presented with UGIB due to corrosive burn (harpic) which was mostly due to suicidal attempt.…”
Section: Discussionmentioning
confidence: 56%
“…In the study of Mahajan & Chandail 13 68.11% presented with both haematemesis and melaena while 20.95% presented with haematemesis only, and 10.94% had melaena only. In the study of Anand et al 11 27.19% patients presented with haematemesis, 12.28% patients presented with isolated melaena, 0.87% patient presented with haematochezia and 59.64% patients presented with complaints of haematemesis and melaena.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Similar prevalence studies are done in India as well as from other developing countries. [9][10][11][12][13][14][15][16][17] As studies are from different geographical locations and having different infrastructural facilities, results in relation to causes, clinical profile and outcome may vary. Table no 6 shows analysis of different studies having almost similar objectives of their research.…”
Section: Discussionmentioning
confidence: 99%